2011
DOI: 10.1016/j.jaad.2010.08.033
|View full text |Cite
|
Sign up to set email alerts
|

A new American Joint Committee on Cancer staging system for cutaneous squamous cell carcinoma: Creation and rationale for inclusion of tumor (T) characteristics

Abstract: Background The incidence of cutaneous squamous cell carcinoma (cSCC) is increasing. Although most patients achieve complete remission with surgical treatment, those with advanced disease have a poor prognosis. The American Joint Committee on Cancer (AJCC) is responsible for the staging criteria for all cancers. For the past 20 years, the AJCC cancer staging manual has grouped all nonmelanoma skin cancers, including cSCC, together for the purposes of staging. However, based on new evidence, the AJCC has determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
161
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(170 citation statements)
references
References 55 publications
3
161
2
4
Order By: Relevance
“…Characteristics of aggressive primary skin cancers in our population are consistent with studies that found similar findings in SOTRs 18 . Farasat et al 19 concluded that up to 20% of high-risk SCCs in SOTRs may metastasize. SCCs were characterized as high-risk if they were poorly-differentiated or had perineural invasion, both of which were seen in our population 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of aggressive primary skin cancers in our population are consistent with studies that found similar findings in SOTRs 18 . Farasat et al 19 concluded that up to 20% of high-risk SCCs in SOTRs may metastasize. SCCs were characterized as high-risk if they were poorly-differentiated or had perineural invasion, both of which were seen in our population 20 .…”
Section: Discussionmentioning
confidence: 99%
“…O grande passo da 7ª edição da classificação da AJCC foi separar o estadiamento do CEC de outros tumores cutâneos, e aproximá-lo do estadiamento dos tumores de cabeça e pescoço, tendo em conta a maior prevalência do CEC nessa área anatómica. 22 Contudo, ambas as classificações são consideradas ineficazes pelas seguintes razões:…”
Section: Carcinoma Espinocelularunclassified
“…16 19 (embora a classificação de AJCC na sua 7º edição sugira aos clínicos acrescentar a letra I, no final da classificação TNM, mas sem quantificar o seu significado para o prognóstico). 22 A classificação da AJCC prevê vários critérios classificados como de "alto-risco", cuja soma faz a distinção entre os está-dios T1 e T2. Porém, tal modelo é considerado de difícil aplicabilidade clínica, e difícil validação estatística, já que implica a divisão dos doentes por uma grande variedade de grupos, tornando as amostras em estudo muito pequenas para validação.…”
Section: Carcinoma Espinocelularunclassified
“…In the sixth edition of the AJCC edition, the limit of 5 cm separated the tumors in T2 and T3, however this limit did not have enough evidence to be sustained and was abolished in the seventh edition, being replaced by parameters more related to the invasiveness than the diameter of tumor (Farasat, Yu et al 2011). …”
Section: Advanced Tumors: Characteristics Of Primary Tumormentioning
confidence: 99%